Pengaruh Penggunaan Multimedia Interaktif Terhadap Penguasaan Konsep dan Keterampilan Berpikir Kritis Siswa pada Materi Suhu dan Kalor - Sadam Husein; Lovy Herayanti; Gunawan Gunawan (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2015)
This research aims to know the effect of using interactive multimedia towards concepts mastery and critical thinking skill of students on the material of temperature ang heat. This research is an experimental research that uses pretest-posttest control design. The sample of this research is grade XA and XB students of SMAN 1 Alas in the academic year 2013/2014 that determined by cluster random sampling technique. The instruments that used to collect the data are test sheets of mastering concepts is developed based on indicator of temperature and heat learning material on the sub topic of expansion, heat transfer and black principle. Meanwhile, the test of critical thinking skill is developed based on the indicator of argument analysis shows that mean score of concepts mastery of experimental group is 61% and control group is 54%. The result of t-test of concepts mastery and critical thinking skill shows that experimental group is significantly higher that control group. It means that the use of interactive multimedia has an effect towards concepts mastery and critical thinking skill of students on the material of temperature and heat.